Gratitude and Resilience among Adolescents Who Have Experienced Parental Divorce - Shabrina, Khairunnisa; Kusristanti, Chandradewi; Listiyandini, Ratih Arruum (Psychological Research on Urban Society, 2020)
Compared to other cities in Indonesia, DKI Jakarta, as one of the largest urban areas, is ranked quite high in divorce rates. It is known that parental divorce has several impacts on children. For example, adolescents with divorced parents have a greater risk of various psychological problems. Previous studies have shown that gratitude enhances positivity and optimism, and it also helps individuals through difficult times, including parental divorce. This non-experimental study aims to determine the role of gratitude in resilience among adolescents (12 – 21 years old) based in the Jakarta metropolitan area (Jabodetabek), whose parents are divorced. Non-probability sampling was used to recruit the participants (n = 109). The measurements used in this study are the Connor-Davidson Resilience Scale (α = 0.896) and Gratitude Scale Indonesian Version (Skala Bersyukur Versi Indonesia (SBI)) (α = 0.896). Simple linear regression showed that gratitude plays a significant role in a participant’s resilience (p < 0.05). Further, 28.9% of the variance in resilience can be explained by gratitude. These findings highlight the importance of gratitude interventions to enhance resilience among adolescents with divorced parents.